Fibronectin adsorption and cell response on electroactive poly(vinylidene fluoride) films - Ribeiro, C. (2012)
Due to the large potential of electroactive materials in novel tissue engineering strategies, the aim of this work is to determine if the crystalline phase and/or the surface electrical charge of electroactive poly(vinylidene fluoride), PVDF, have influence on the biological response in monolayer cell culture. Non-polar -PVDF and electroactive -PVDF were prepared. The -PVDF films were poled by corona discharge to show negative or positive electrical surface charge density. It has been concluded that hydrophilicity of the PVDF substrates depends significantly on crystalline phase and polarity. Further, by means of AFM and ELISA test it has been shown that positive or negative poling strongly influences the behaviour of -PVDF supports with respect to fibronectin adsorption, varying the exhibition of adhesion ligands of adsorbed fibronectin. Culture of MC3T3-E1 pre-osteoeblasts proved that cell proliferation depends on surface polarity as well. These results open the viability of cell culture stimulation by mechanical deformation of a piezoelectric substrate that results in varying electrical charge densities on the substrate surface.